DETERMINANTS OF MUZZAKI'S INTEREST IN PAYING ZAKAT IN BAITUL MAL - Tri Aulia; Muhammad Salman; Nasrul Kahfi Lubis; Nurliza Lubis (RADJA PUBLIKA, 2022)
This study was conducted to determine the determination of muzzaki's interest in making zakat in Baitul Mal. The research was conducted in Baitul Mal Aceh Tamiang. This type of research is quantitative. This study used probability sampling by cluster sampling. The sample used was muzakki in 12 sub-districts in Aceh Tamiang Regency as many as 100 respondents. Data collection techniques using questionnaires. The data analysis method uses multiple linear regression, classical assumption test, and hypothesis test. The results of the study with partial tests showed that the determinants of muzzaki's interest as independent variables, namely zakat literacy, religiosity, and regulation had a positive and significant effect on muzzaki's interest in paying zakat through Baitul Mal Aceh Tamiang Regency. The results simultaneously showed that the determinants of muzzaki's interest in paying zakat, namely zakat literacy, religiosity, and regulation together had a significant positive effect on muzzaki's interest in paying zakat through Baitul Mal Aceh Tamiang Regency.